1986
DOI: 10.1001/jama.1986.03380240058028
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Lung Cancer Patients Requiring Mechanical Ventilation for Pulmonary Failure

Abstract: The prognosis of lung cancer patients who are not candidates for surgery is usually poor. The unfavorable natural history of respiratory failure in this group of patients has been suggested as a causative factor. We analyzed the outcome of 46 consecutive patients with primary lung cancer on whom mechanical ventilators were utilized. Although seven patients were ultimately weaned and survived for at least 24 hours, three of them subsequently died prior to discharge from the hospital. The remaining 39 patients d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
3

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(36 citation statements)
references
References 9 publications
2
30
1
3
Order By: Relevance
“…The present study shows that the outcome of lung cancer patients admitted to the MICU has improved significantly compared with historical studies and confirms the findings of a recent study on a similar group of patients from Brazil and France (table 6) [22][23][24][25][26]30]. Furthermore, the present study shows that the mortality rate for those lung cancer patients who require MV is higher than that for the group as a whole; however, the MICU outcome of these patients showed a similar favourable trend compared with previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study shows that the outcome of lung cancer patients admitted to the MICU has improved significantly compared with historical studies and confirms the findings of a recent study on a similar group of patients from Brazil and France (table 6) [22][23][24][25][26]30]. Furthermore, the present study shows that the mortality rate for those lung cancer patients who require MV is higher than that for the group as a whole; however, the MICU outcome of these patients showed a similar favourable trend compared with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…In the study by LIN et al [24], on the outcome of lung cancer patients with acute respiratory failure requiring MV, the MICU mortality was 73% and the in-hospital mortality was 85%. Another study by EWER et al [25] reported the in-hospital mortality to be as high as 91% and a 6-month mortality of 98%. In the recent study by SOARES et al [30], the MICU mortality rate for lung cancer patients who required MV was 56% and the in-hospital mortality was 69%.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The mortality rate among lung cancer patients admitted to the intensive care unit (ICU) has dropped from 85% in 1986 [1] to 22-47% in 2005 [2][3][4][5][6]. These survival gains are ascribable to improvements in anticancer drugs [7][8][9] and intensive care [10], as well as to changes in criteria for ICU admission [11].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies showed that these systems underestimate mortality and are not a useful predictor of outcome in patients with malignancy, including lung cancer [13]. The need for mechanical ventilation is another variable that has been studied and proven to be an important predictor of poor ICU and hospital outcome in lung cancer patients [9,10,14]. The difference in survival is significant between critically ill lung cancer patients who are mechanically ventilated and those who are not (hospital mortality: 53 vs 27%, respectively) [2].…”
Section: Future Oncol (2008) 4(2)mentioning
confidence: 99%